Dinamika Makna Qawwām: Analisis Mufasir Perempuan terhadap Surah An-Nisā: 34 - Muhammad Fajar Adyatama; Sujiat Zubaidi Saleh; Nofriyanto Nofriyanto; Fachri Khoerudin (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2023)
The first part of the 34th verse of Surah An-Nisā, the verse on qawwām, explains the role of men as leaders for their wives and children. His position as the head of the family makes him responsible for providing for, protecting, nurturing and striving for the benefit of the family. However, in the early 20th century, some muslim feminists who were influenced by Western gender equality ideology rejected the interpretation of qawwām that made men the leader or head of the family. According to them, the interpretation of qawwām by classical mufassirs, the majority of whom were men, was gender biased. This article tries to review the meaning and function of qawwām in the view of female mufassirs with the aim of presenting a commensurate argument for feminist criticism of the interpretation of qawwām by classical mufassirs.  This study uses a library research approach that contains the meaning and function of qawwām from many figures, but the focus is on the interpretation of qawwām from female mufassirs. The results of this study reveal that the interpretation of female mufassirs regarding the verse on qawwām is not different from the classical mufassirs. This means that the classical mufassirs' interpretation of qawwām is not gender biased as feminists claim.